2021
DOI: 10.3899/jrheum.201299
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Peripheral Neuropathy in Systemic Sclerosis

Abstract: Objective The epidemiology and treatment of peripheral neuropathy in systemic sclerosis (SSc) is poorly understood. The objectives of this study were to evaluate the incidence, prevalence, risk factors, and treatments of peripheral neuropathy in SSc. Methods A systematic review of Medline, Embase and CINAHL databases for literature reporting peripheral neuropathy in SSc was performed. Studies evaluating incidence, prevalence, risk factors, and treatments were synthesized. Meta-analysis using a random effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 88 publications
0
17
0
1
Order By: Relevance
“…(7) Lesions may be asymptomatic, or associated with pain, soft tissue swelling, ulcers with superimposed infections, or even deformities leading to functional disability (5). Calcinotic lesions can lead to compression neuropathies resulting in motor and/or sensory deficits (34). Ulceration of the overlying skin may occur, with a higher tendency in the forearm, elbows, fingers (particularly the volar aspect of fingertips), the metacarpophalangeal or the interphalangeal joints.…”
Section: Evaluation and Diagnosis Of Calcinosismentioning
confidence: 99%
“…(7) Lesions may be asymptomatic, or associated with pain, soft tissue swelling, ulcers with superimposed infections, or even deformities leading to functional disability (5). Calcinotic lesions can lead to compression neuropathies resulting in motor and/or sensory deficits (34). Ulceration of the overlying skin may occur, with a higher tendency in the forearm, elbows, fingers (particularly the volar aspect of fingertips), the metacarpophalangeal or the interphalangeal joints.…”
Section: Evaluation and Diagnosis Of Calcinosismentioning
confidence: 99%
“…Furthermore, the materials and methods used in those studies provide a large range of results. A recent systematic review of 113 studies [4] showed a pooled prevalence of neuropathy involvement in 27.37% of cases, including 26% (n = 556/2,143) with SFN and 10.8% (n = 231/2,143) with LFN when neuropathies were assessed based on small and large fibres.…”
Section: Discussionmentioning
confidence: 99%
“…trigeminal neuropathy, carpal tunnel syndrome, ulnar nerve entrapment) and non-compression (e.g. sensorimotor neuropathy, sensory ataxic neuropathy, multiple mononeuropathies) neuropathies [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to PNs, in a cross-sectional study by Raja et al ( 73 ) and Paik et al ( 74 ), the prevalence of PN in SSc varied from 28 to 36.6%. In a recent systematic review from AlMehmadi et al ( 75 ), compression neuropathies were reported in 26.5% of the studies, and according to Yagci et al ( 76 ) and Sriwong et al ( 77 ), the prevalence of median neuropathy in SSc is estimated to be 35%. Most CTS in patients with SSc were asymptomatic.…”
Section: Neuropathies In the Most Common Acquired Rheumatological Con...mentioning
confidence: 99%